Modifiable and Non-modifiable Factors Associated with Low Awareness of Hypertension Treatment in Indonesia: A Cross-Sectional Population-Based National Survey - Qisty A. Khoiry; Sofa D. Alfian; Rizky Abdulah (Ubiquity Press, 2022)
Introduction: Low awareness about hypertension treatment is recognized as a significant cause of treatment failure. Therefore, identifying its underlying factors is essential for developing effective intervention strategies. This study aims to identify the modifiable and non-modifiable factors associated with low awareness about hypertension treatment. Method: This national, cross-sectional, population-based survey used publicly available data from the Indonesian Family Life Survey (IFLS-5) for 2014 among respondents with hypertension aged ≥15 years. Depression and insomnia, as modifiable factors, were assessed using the Centre for Epidemiologic Studies-Depression (CES-D) and the Patient-Recorded Outcomes Measurement Information System (PROMIS) questionnaire, respectively. Non-modifiable factors, such as sociodemographic information, were obtained from self-reported data. Logistic regression analysis was used to assess the association between these factors and low awareness about hypertension treatment. Odds ratios (ORs) with 95% confidence intervals (CIs) were reported. Result: The study recruited 7,920 respondents, the majority of whom were female (53.8%) and aged <60 years (71.1%). The prevalence of low awareness of hypertension treatment was 87.1% (51.8% in women and 48.2% in men). Being an elderly (OR: 1.60, 95%CI 1.36-1.88), being irregularly blood pressure control (OR: 4.40, 95% CI 3.78-5.13), having depressive symptoms (OR: 1.35, 95% CI 1.12-1.62), having insomnia (OR: 1.31, 95% CI 1.11-1.53), and having low satisfaction with health care (OR: 1.28, 95% CI 1.08-1.51) were associated with low awareness of hypertension treatment. Surprisingly, respondents with strong religiosity (OR: 1.62; 95% CI 1.25-2.09) were more likely to display low awareness of hypertension treatment. Conclusion: The main factors associated with low awareness of hypertension treatment are modifiable. Thus, health care professionals should integrate more patient-specific factors when designing tailored interventions.